Cooperative work and vocational rehabilitation in the drug addiction treatment: opportunities and limitations of current practices - Bonadio, Alessandra Nagamine; Silveira, Cássio (Saúde e Sociedade, 2013)
This paper contributes to the debate on the potencial of work in the recovery process of addicts. The vocational rehabilitation principles are analyzed and compared to the Brazilian guidelines for the work rehabilitation of this population. In this analysis we compare the underlying concept of health and the emancipatory potential in both perspectives. The literature on vocational rehabilitation was raised through a literature review on Medline, Pubmed and Lilacs, with the following key words: vocational rehabilitation, substance abuse treatment & work. The Brazilian Government guidelines were collected in the official publications available online by the Ministry of Health and Ministry of Labour and Employment of Brazil. The analysis of the material pointed out that the vocational rehabilitation practiced in North America and Europe focus on users of mental health services, proceeding to the work inclusion through the bias of the disease. The vocational rehabilitation emphasizes the replacement in the formal labor market, through programs aimed at skills training to get and keep a job. On the other hand, the Brazilian public policies are guided by the principles of cooperative and social economy. It privileges the human ethics in its entirety, as the subject and the purpose of higher economic activity, focusing on the strengths and resources of the work, rather than the limitations imposed by the disease or the socioeconomic status that has generated the situation of exclusion.